2017
DOI: 10.1097/shk.0000000000000801
|View full text |Cite
|
Sign up to set email alerts
|

Does Respiratory Variation in Inferior Vena Cava Diameter Predict Fluid Responsiveness

Abstract: Respiratory variation in IVC diameter has limited ability to predict fluid responsiveness, particularly in spontaneously ventilating patients. A negative test cannot be used to rule out fluid responsiveness. Clinical context should be taken into account when using IVC ultrasound to help make treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
3
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(136 citation statements)
references
References 82 publications
4
117
3
12
Order By: Relevance
“…Intra‐observer variability in our study compared favourably to that reported in previous studies (<10% for IVC collapsibility index measurement and <5% for stroke distance measurement) …”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Intra‐observer variability in our study compared favourably to that reported in previous studies (<10% for IVC collapsibility index measurement and <5% for stroke distance measurement) …”
Section: Discussionsupporting
confidence: 85%
“…Multiple studies in spontaneously ventilating adults have reported the accuracy of respiratory variation in IVC diameter as a predictor of fluid responsiveness, [34][35][36][37][38][39][40] with a pooled AUROC of 0.76. 24 The majority of these studies enrolled mixed patient populations, including those with trauma, dehydration and postoperative surgical patients. The haemodynamic response to FBT in patients with systemic inflammation may differ from that observed in patients with fluid loss; 27 endothelial dysfunction may significantly influence the rate of fluid shift out of the intravascular compartment and the duration of effect of FBT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Early inferior vena cava studies showed great correlations between inferior vena cava collapsibility indices and patients’ central venous pressure. Although some studies did show some correlation with volume responsiveness in intubated patients, it did not predict fluid responsiveness in spontaneously breathing patients . More recently, intensive care physicians have looked at the role of noninvasive echocardiography as a measure of volume responsiveness in intensive care units.…”
Section: Discussionmentioning
confidence: 99%
“…While the IVC collapsibility index (IVCCI) has initially shown promising results in mechanically ventilated patients,40 41 studies in spontaneously breathing patients suggest a limited role 42 43. There is considerable interobserver variation44 and while an IVCCI >30%–50% identifies patients likely to improve stroke volume with additional fluid loading, patients with lower levels of collapse <30%–50% may or may not benefit from additional fluid 42…”
Section: Assessment Of Volume Statusmentioning
confidence: 99%